NEWLY DISCLOSED CIRCUMSTANCES – GROUNDS FOR RENEWAL OF CRIMINAL PROCEEDING - Baikovska, Inese (Administrative and Criminal Justice, 2018)
It is presumed that no appeal may lie from a judgment that has already entered into legal force and such a judgment is regarded as final in a case, criminal proceedings may still be reopened under certain legal circumstances, which are called newly discovered. This is how the right of persons involved in criminal proceedings to a fair trial and a fair final judgment is ensured.The goal of this article is to examine circumstances that can be recognised as newly discovered and serve as grounds for the reopening of criminal proceedings, identify problems related to legal framework and find a legally sound solution. The tasks of this article are to investigate provisions applied to newly discovered circumstances as defined by the Criminal Procedure Law. As a result of the research, the author has concluded that the Latvian legislation governing criminal procedure with respect to the definition of newly discovered circumstances is deficient; therefore, suggestions are provided for the improvement of the existing legal framework. The research is based on the analysis of legislation, judgments of courts, conclusions and separate opinions of judges.